Mechanistic Insights into Ferredoxin–NADP(H) Reductase Catalysis Involving the Conserved Glutamate in the Active Site - Dumit, Veronica Ines (2010)
Plant-type ferredoxin?NADP(H) reductases (FNRs) are flavoenzymes harboring one molecule of noncovalently bound flavin adenine dinucleotide that catalyze reversible reactions between obligatory one-electron carriers and obligatory two-electron carriers. A glutamate next to the Cterminus is strictly conserved in FNR and has been proposed to function as proton donor/acceptor during catalysis. However, experimental studies of this proposed function led to contradicting conclusions about the role of thisglutamate in the catalytic mechanism. In the present work, we study the titration behavior of the glutamate in the active site of FNR using theoretical methods. Protonation probabilities for maize FNR were computed for the reaction intermediates of the catalytic cycle by Poisson?Boltzmann electrostatic calculations and Metropolis Monte Carlo titration. The titration behavior of the highly conserved glutamate was found to vary depending on the bound substrates NADP(H) and ferredoxin and also on the redox states of these substrates and the flavin adenine dinucleotide. Our resultssupport the involvement of the glutamate in the FNR catalytic mechanism not only as a proton donor but also as a key residue for stabilizing and destabilizing reaction intermediates. On the basis of our findings, we propose a model rationalizing the function of the glutamate in the reaction cycle, which allows reinterpretation of previous experimental results.